One of the Methods and Ways of Dialect Word Formation - Khaknazarovich, Nabiyev Rajabboy (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses one of the methods and methods of word formation of the dialect that are the object of research, in which there are significantly more words-terms formed phonetically than in other Uzbek dialects. Due to the fact that the government of our country has set the task of organizing scientific expeditions on the territory of the republic in order to collect folklore materials and folk legends that are the property of the Uzbek language, opportunities are opening up for a wide study of folk legends. There are phonetic, lexical and grammatical manifestations of dialectisms, which are a means of ensuring the identity of the language.